Red Days: Popular Music & the English Counterculture 1965‐1975, John Roberts (2020). (1st June 2022) - Erraught, Stan
Review of: Red Days: Popular Music & the English Counterculture 1965‐1975, John Roberts (2020)Colchester and New York: Minor Compositions, 197 pp., ISBN 978-1-57027-364-3, p/bk, GBP £18.00